Excessive Indoor Tanning as a Behavioral Addiction: A Literature Review - Petit, Aymeric; Lejoyeux, Michel; Reynaud, Michel; Karila, Laurent (Current Pharmaceutical Design, 2014)
Background: Socially valorized, excessive indoor tanning can lead to dependence. This finding is based on the observations of many dermatologists, who report repeated failures in preventing their patients from visiting tanning cabins, despite the announcement of a diagnosis of malignant melanoma. Objective: The objective of this paper is to show that excessive indoor tanning can be included in the spectrum of addictive behavior. This review focuses on the clinical features, diagnosis, prevalence, etiology, treatment, prevention, and psychopathology of this disorder. Methods: A review of the medical literature was conducted using PubMed and Google Scholar and using the following key words alone or in combination: tanning, addiction, dependence, tanning bed, sun exposure, and solarium. We selected 41 English-language articles from 1974 to 2013. Results: Many excessive indoor tanners meet symptom criteria adapted from the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM-IV-TR) substance abuse and dependence criteria. Trial studies suggest that there may be a physiological basis, consisting of dependence on opioids, for excessive indoor tanning behaviors. Conclusion: Excessive indoor tanning can be included in the spectrum of addictive behaviors, although other models may be proposed. Further controlled studies must be performed, especially in neurobiology and imaging, to improve our understanding of tanning dependence.
Keywords: sun exposure